Examining recent shifts in Australia's foreign aid policy: new paradigm or more incremental change?. Issue 1 (2nd January 2016) - Corbett, Jack; Dinnen, Sinclair
ABSTRACT: On taking office in late 2013, the incoming Abbott government proclaimed the advent of a new aid paradigm. This article asks whether or not this is the case. It does so by situating the new coalition policy in the context of more than two decades of development thinking. Focusing on the way Australian aid policy reflects trends in both global development and geopolitical discourses, the article parses out continuity and change. It finds that Australia's new aid paradigm is in fact largely the old aid paradigm reincarnate, with aid policy continuing to follow the well-established parameters outlined over decades of global thinking and practice that emphasise the significance of private-sector-led economic growth. However, while the overarching paradigm remains relatively intact, incremental change is also apparent, including alterations to the geographic focus, level and administration of the program.